Faktor-Faktor Yang Mempengaruhi Penerapan Standar Akuntansi Pemerintahan (SAP) Berbasis Akrual - Anita De Grave; Syahril Hasan (Akuntabilitas, 2022)
This study aimed at determining how the effect of the variabels of human resources’ quality, organizational commitment, and SIPKD on the implementation of accrual-based Government Accounting Standards in the Government of Balikpapan City district both partially and simultaneously. The population of the unit of analysis in this study was 18 official governments in Balikpapan City. The sampling was through the purposive sampling technique with total respondents of 72 people. The data collection was conducted through a questionnaire and the measurement was conducted through a Likert scale. The results of this study are partial, the variabel of the quality of human resources, organizational commitment, and SIPKD significantly affected the implementation of accrual-based Government Accounting Standards in the Government of Balikpapan City. Simultaneously, the quality of human resources, organizational commitment, and SIPKD significantly affected the implementation of accrual-based Government Accounting Standards in the Government of Balikpapan City.